Effects of using different dentin conditioners on dentin regeneration: Dentine conditioners effect on dentine regeneration - Saeed Khidir, Hiwa; Sherdl Saleem, Sazan (Cellular and Molecular Biology, 2024)
This experiment aimed to evaluate the impact of several dentine etching and conditioning agents on growth factors (GFs) liberation from dentine slices. Eighteen dentine slices were obtained from nine premolars divided in to six groups, the slices immersed in one mL test solutions for 5 min; Group 1: white Mineral trioxide aggregate (MTA), Group 2: Phosphate buffered saline (PBS), Group 3: 37% phosphoric acid, Group 4: 17% Ethylenediaminetetraacetic Acid (EDTA), Group 5: 10% Maleic acid (MAc), and Group 6: 0.7% Fumaric acid. The solutions were removed and stored directly at for further detection and quantification of transforming GF beta 1 (TGF-b1), bone morphogenetic protein 2 (BMP2) and vascular endothelial growth factor (VEGF) by enzyme-linked immunosorbent assay (ELISA). One-way ANOVA was used to compare the mean release and standard deviation between groups (α = 0.05). Tukey’s post hoc applied for multiple comparisons. After five min conditioning of dentine slices, white MTA released the highest level of TGF-b1, BMP2 and VEGF among all groups, followed by 0.7% Fumaric acid with no significant difference between them, but compared to 37% phosphoric acid and PBS groups significant difference observed, which they released the least amount of GFs amongst all groups. Based on the results of this research the detectable release of TGF-b1, BMP2 and VEGF by 0.7% fumaric acid was comparable with white MTA from dentin slices.